2021
DOI: 10.1186/s40345-021-00238-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of affective lability across subgroups of psychosis spectrum disorders

Abstract: Background Affective lability is elevated and associated with increased clinical burden in psychosis spectrum disorders. The extent to which the level, structure and dispersion of affective lability varies between the specific disorders included in the psychosis spectrum is however unclear. To have potential value as a treatment target, further characterization of affective lability in these populations is necessary. The main aim of our study was to investigate differences in the architecture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…In the bipolar spectrum group, on the other hand, affective lability remained significantly and independently associated with social functioning even when the other predictors were taken into account. Nonetheless, as our previous study showed that the level of affective lability is significantly different in BDI versus BDII disorders [ 22 ], this finding warrants further investigation in larger samples to tease out if the association between affective lability and social functioning is the same irrespective of bipolar subtype.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…In the bipolar spectrum group, on the other hand, affective lability remained significantly and independently associated with social functioning even when the other predictors were taken into account. Nonetheless, as our previous study showed that the level of affective lability is significantly different in BDI versus BDII disorders [ 22 ], this finding warrants further investigation in larger samples to tease out if the association between affective lability and social functioning is the same irrespective of bipolar subtype.…”
Section: Discussionmentioning
confidence: 72%
“…Albeit accounting for a modest part of the total variance, this association remained at a level of statistical significance even when we controlled for other well-established predictors of social functioning such as premorbid social functioning, duration of untreated illness, and level of current symptoms. We have previously found that affective lability in our sample was characterized by fluctuations between both anxiety-depression and depression-elation across diagnostic groups [ 22 ]. However, only fluctuations between anxiety- and depressive symptoms appear to be directly linked to social functioning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Affective lability is also seen in psychotic spectrum disorders, though more familiar to clinicians in the setting of bipolar spectrum disorders. A recent study identified no significant differences in affective lability between bipolar I disorder vs. schizophrenia patients [ 55 ].…”
Section: Discussionmentioning
confidence: 99%